Marcusa Vogta próba integracji zasad ekorozwoju z Katolicką Nauką Społeczną - Rafał Czekalski (Studia Ecologiae et Bioethicae)
In this article, we have attempted to answer the question of the possibilities of integrating the principles of eco-development with Catholic social teaching. We have done so on the basis of the works of a German moral theologian M. Vogt. The integration of the principles of eco-development with the Catholic social teaching may take place in a dialogue between the theology of creation together with its implications and the knowledge of nature. Considering the issue from the socio-ethical perspective it is vital to work out a new social agreement, which would take into account justified, although unspecified, claims of future generations. The integration of the principles of eco-development with Catholic social teaching is by no means impossible, although Vogt warns against treating the concept of eco-development as a superior issue - it is not a solution itself, but rather a key to the solution of contemporary problems at an intersection of three dimensions: social, economic and ecological. The proposed principle of eco-development shall become autonomous not in isolation to the traditional principles of Catholic social teaching, but in relation to them. The novelty of this principle is more about a new perspective, where man has to learn to see himself as part of creation as a whole. The principle also calls for a new way of thinking, which is the transition from a linear to a network way of thinking.